Growth, phenology, and yield components of barley and wheat grown in Alaska - Dofine, S. M. (Canadian Journal of Plant Science, 1992)
The comparative growth, phenology, and yield components of three early-maturing barley (Hordeum vulgare L.) and wheat (Triticum aestivum L.) cultivars were studied during the 1989–1991 growing seasons at Palmer, Alaska. Barley cultivars produced an average of 1.1 more leaves than wheat, and had a smaller (4.5 growing degree days/leaf) phyllochron interval. The early maturity of barley relative to wheat was due mainly to its ability to fill and ripen grain under cool conditions.Key words: Barley, wheat, subarctic, phyllochron